Pigouvian taxation in a Ramsey world - Robin Boadway; Jean-Francois Tremblay (Queen's University, Department of Economics, 2008)
This paper studies the optimal Pigouvian tax for correcting pollution when the government also uses distortionary taxes to raise revenues. When preferences are quasilinear in leisure and additive, the Pigovian tax can be separated from the Ramsey revenue-raising tax. We characterize the relationship between the Pigouvian tax and marginal social damages in a variety of circumstances. In a setting with homogeneous households, the Pigouvian tax exceeds marginal damages if goods have inelastic demands, and vice versa. When households are heterogeneous so taxes can be redistributive, the Pigouvian tax gives more weight to damages suffered by low-income persons. The analysis is extended to allow for costly abatement. In general corrective taxes have to be applied to both emissions and output of the polluting good.
Keywords: H21; H23; 330; pigouvian tax; optimal taxes; pollution tax; Steueraufkommen; Optimale Besteuerung; Ökosteuer; Wohlfahrtsanalyse; Theorie